2013
DOI: 10.1111/jpn.12050
|View full text |Cite
|
Sign up to set email alerts
|

Feeding a diet contaminated with ochratoxin A for chickens at the maximum level recommended by the EU for poultry feeds (0.1 mg/kg). 1. Effects on growth and slaughter performance, haematological and serum traits

Abstract: SummaryThe European Commission Recommendation 2006/576/EC, suggests that the maximum level of Ochratoxin A (OTA) in poultry feeds should be set at 0.1 mg OTA/kg. Thirty-six one-day-old male Hubburd broiler chickens were divided into two groups, a Control (basal diet) and an Ochratoxin A (basal diet + 0.1 mg OTA/kg) group. The growth and slaughter performance traits were recorded. The liver, spleen, bursa of Fabricius and thymus weights were measured. The erythrocyte and leukocyte numbers were assayed in blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 54 publications
4
30
0
Order By: Relevance
“…These results suggest that the maximum level of OTA set by the European Recommendation for poultry feed did not completely prevent histopathological lesions in the immune organs of broiler chicks. These results agree with the data obtained in the first part of the study (Pozzo et al.,) that, for OTA‐treated chicks, reported a decrease in thymus weight and in total protein, albumin, alpha, beta and gamma globulin serum concentration. However, Kozaczynski showed that long‐term (20 week) administration of 0.2 mg OTA/kg in feed, at twice the concentration used in the present study, caused no histopathological lesions (Kozaczynski, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results suggest that the maximum level of OTA set by the European Recommendation for poultry feed did not completely prevent histopathological lesions in the immune organs of broiler chicks. These results agree with the data obtained in the first part of the study (Pozzo et al.,) that, for OTA‐treated chicks, reported a decrease in thymus weight and in total protein, albumin, alpha, beta and gamma globulin serum concentration. However, Kozaczynski showed that long‐term (20 week) administration of 0.2 mg OTA/kg in feed, at twice the concentration used in the present study, caused no histopathological lesions (Kozaczynski, ).…”
Section: Discussionsupporting
confidence: 92%
“…The two groups received two different diets, and three replicates per diet were used: the control group received the basal diet (a soybean meal, wheat‐ and corn‐based diet; first period: metabolizable energy: 13.1 MJ/kg and crude protein = 230.5 g/kg; second period: metabolizable energy = 13.5 MJ/kg and crude protein = 195.0 g/kg), while the ochratoxin A group received an OTA‐contaminated diet (0.1 mg OTA/kg added to the basal diet). The contamination of feed and the results of homogeneity test are described in Part 1 of the present study (Pozzo et al., ). Control diet was naturally contaminated at a level of 0.27 ± 0.09 μg OTA/kg.…”
Section: Methodsmentioning
confidence: 99%
“…LDH of a and c groups, and AST of c group were lower in the highdose than the control rats, which were consistent with previous reports 14,15 . In contrast, ALB activity of c group was slightly higher in high-dose group than in control rats 13 .…”
Section: Resultssupporting
confidence: 82%
“…An ''in-silico'' screening of miRNA binding site prediction was carried out within deregulated genes by adopting the miRWalk database 15 , including miRanda, miRDB, miRWalk, PITA, TargetScan and RNAhybrid. The targets predicted by at least two different programs were chosen for further analysis to effectively reduce false positive targets 13,[17][18][19][20][21][22] .…”
Section: Wwwnaturecom/scientificreportsmentioning
confidence: 99%
“…Scientific literature reports several experiments in which tissues and organs from poultry experimentally exposed to OTA were analysed [20,[38][39][40][41] but only few survey studies were carried out to monitor the presence of OTA in tissues of animals normally reared on poultry farms.…”
Section: Discussionmentioning
confidence: 99%